Assistance in the Production of Cracker Snacks in the Cileungsi Area - Wilarso; Aswin Domodite; Ika Novalia Saputri; M Ali Pahmi; Hanifah Syayidah Lutfiyah (Direktorat Penelitian dan Pengabdian Kepada Masyarakat, 2021)
Snack food production has its characteristics in the community, in the manufacture of food, there are often obstacles, ranging from raw materials, manufacturing methods, and capital. The purpose of this community service is to increase the added value of the production of cracker snacks made from tofu and rice, to become rainbow crackers in UMKM-Cileungsi. The method of implementing community service is assistance in designing the cracker production process, testing the production process, mentoring, and training to make tofu crackers and rainbow crackers. The attention of UMKM and the community regarding PKM is considered positive and can make a very good contribution to the surrounding community. so that they have creative ideas in creating superior products with various flavors & shapes from easily available raw materials. At the same time providing new business opportunities